Meeting measles elimination indicators: surveillance performance in a regional area of Australia - Kohlhagen, Julie; Massey, Peter; Durrheim, David (Western Pacific Surveillance and Response, 2013)
The World Health Organization (WHO) Western Pacific Region has established specific measles elimination surveillance indicators. There has been concern in Australia that these indicators may be too stringent and that measles elimination can occur without all surveillance prerequisites being met, in particular the minimum fever and rash clinician-suspected measles reporting rate with subsequent laboratory exclusion of measles. A regional public health unit in northern New South Wales, Australia, prompted local general practitioners to report fever and rash presentations that met the measles case definition or that they considered to be clinical measles. These notifications from July 2006 to June 2008 were reviewed to determine whether measles indicators for monitoring progress towards measles elimination could be achieved in Australia. Results confirmed that the surveillance indicators of “>2 reported suspected measles cases per 100 000 population,” “at least 80% of suspected cases adequately investigated within 48 hours” and “greater than 80% of cases had adequate blood samples collected” could be met. Only half the cases had virology that would allow genotyping of measles virus. Special efforts to engage and convince Australian medical doctors about the public health value of reporting clinically suggestive measles cases and collecting confirmatory blood tests, resulted in the current WHO Western Pacific Region indicators for progress towards measles elimination being met in a regional area of Australia.